2000
DOI: 10.1111/j.1465-7295.2000.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

A theory of quality‐related differences in retail margins: why there is a ‘premium’ on premium gasoline

Abstract: This paper develops a theory of vertical and horizontal product differentiation to explain observed price-cost margin differentials for goods that differ in quality. The difference in price-cost margins between the high-and low-quality good is shown to depend positively on consumers' average valuation for incremental increases in quality and positively on the distance to each competitor's closest rival. These predictions are largely supported using an extensive station-level data set of premium and regular unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
(24 reference statements)
1
32
0
Order By: Relevance
“…Lach (2002) finds very similar results in a sample of retail prices of consumer goods in Israel; i.e., the relative position of a retailer in the pricing distribution changes frequently.4 For papers examining retail gasoline pricing in a cross section or short panel see,Slade (1992),Shepard (1990Shepard ( , 1991Shepard ( , 1993,Barron et al (2000Barron et al ( , 2004,and Hastings (2004).…”
mentioning
confidence: 58%
“…Lach (2002) finds very similar results in a sample of retail prices of consumer goods in Israel; i.e., the relative position of a retailer in the pricing distribution changes frequently.4 For papers examining retail gasoline pricing in a cross section or short panel see,Slade (1992),Shepard (1990Shepard ( , 1991Shepard ( , 1993,Barron et al (2000Barron et al ( , 2004,and Hastings (2004).…”
mentioning
confidence: 58%
“…Thus, drivers of more expensive cars are more likely than owners of less expensive cars to purchase premium gasoline. Luxury car owners tend to have higher incomes, and Barron et al (2000) present evidence that high income consumers that purchase premium fuel are typified by greater search costs. Consumers that purchase premium fuel pay a large markup for a product that offers almost no perceptible benefit over regular fuel.…”
Section: When Consumers Search Less-the Case Of Premium Fuelmentioning
confidence: 96%
“…In general, these studies find evidence of price discrimination according to local income levels and through service levels (e.g. Shepard), as well as evidence that station characteristics, location, and local competition affect stationlevel pricing (e.g., Plummer et al, 1998;Barron et al, 2000). In contrast to Barron et al (2000), Hastings (2002) found that station level after-tax margins decrease with the incomes of local consumers and that the conversion of independent stations in Los Angeles and San Diego to the ARCO brand resulted in an increase in retail prices, relative to unaffected markets.…”
Section: Existing Evidence On Retail Gasoline Pricingmentioning
confidence: 97%
“…(See, for example, Noel, 2001. ) Other studies have large cross sections of stations, but either study prices for a short period (Shepard, 1991) or have access only to prices surveyed with a frequency of no more than once per week (Haining, 1983;Plummer et al, 1998;Barron et al, 2000).…”
Section: Introductionmentioning
confidence: 98%